2017
DOI: 10.1080/17435390.2017.1306892
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative biokinetics of titanium dioxide nanoparticles after intravenous injection in rats: Part 1

Abstract: Submicrometer TiO particles, including nanoparticulate fractions, are used in an increasing variety of consumer products, as food additives and also drug delivery applications are envisaged. Beyond exposure of occupational groups, this entails an exposure risk to the public. However, nanoparticle translocation from the organ of intake and potential accumulation in secondary organs are poorly understood and in many investigations excessive doses are applied. The present study investigates the biokinetics and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 42 publications
7
70
0
Order By: Relevance
“…The biokinetics and biodistribution of nanomaterials following intravenous exposure is different from the biokinetics/biodistribution of nanomaterials administered to the respiratory tract as described earlier . In addition, a very recent series of three publications by Kreyling et al showed that the biokinetics of intravenously injected nanomaterials does not represent a surrogate biokinetic approach for pulmonary or oral routes of exposure . The authors employed 70 nm radiolabeled TiO 2 NPs containing 48 V in rats to study the biokinetics and biodistribution in various tissues over the period of 1 h to 28 d. After intravenous injection, the highest titanium accumulation was found in the liver, followed by the spleen, carcass, skeleton, and blood after 1 h, after which the blood content decreased rapidly, while the distribution in the other organs and tissues remained constant until day 28.…”
Section: Biodistribution and Biokineticsmentioning
confidence: 99%
“…The biokinetics and biodistribution of nanomaterials following intravenous exposure is different from the biokinetics/biodistribution of nanomaterials administered to the respiratory tract as described earlier . In addition, a very recent series of three publications by Kreyling et al showed that the biokinetics of intravenously injected nanomaterials does not represent a surrogate biokinetic approach for pulmonary or oral routes of exposure . The authors employed 70 nm radiolabeled TiO 2 NPs containing 48 V in rats to study the biokinetics and biodistribution in various tissues over the period of 1 h to 28 d. After intravenous injection, the highest titanium accumulation was found in the liver, followed by the spleen, carcass, skeleton, and blood after 1 h, after which the blood content decreased rapidly, while the distribution in the other organs and tissues remained constant until day 28.…”
Section: Biodistribution and Biokineticsmentioning
confidence: 99%
“…Apart from the previously mentioned reasons, ease of synthesis on a nanoscale size is another argument for selection of these two materials. [2][3][4][5][6][7] Our main area of interest is specically the possibility of the application of the chosen nanomaterials as a drug carrier system for diagnostic, therapeutic or theragnostic radionuclides. The targeting of the nanoparticles to the required tissue can be enabled by two mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…17 Hepato-biliary NP clearance turned out to represent a potential excretion route. 18,19 The effect of long-term accumulation in the liver is not clear due to the lack of appropriate investigations. Liver plays a central role in physiological processes in the organism to keep metabolic homeostasis and is the main organ for detoxifying xenobiotics and drugs.…”
Section: Introductionmentioning
confidence: 99%